Vulvar lichen planus - clinical spectrum (results of a cross-sectional uncontrolled study) - Olga V. Parygina; Irina О. Smirnova; Yanina G. Petunova; Yana S. Kabushka; Anton R. Zhelonkin (State Scientific Center of Dermatovenereology and Cosmetology, 2022)
Background. Lichen planus (LP) is a chronic dermatosis, which can affect vulva. Currently, there are no sufficient data about clinical picture of vulvar LP and a valuation combined lesion on the vulva, oral mucous and smooth skin in patients with different forms of LP. Aims. Is to study the features of the vulvar LP clinical picture. Materials and methods. A cross-sectional (simultaneous) uncontrolled study of 46 patients with vulvar LP was performed. We assessed the structure of vulvar LP, the duration and the manifestation of disease, localization of lesions, the involvement of the skin and oral mucosa. LichenSclerosus-Square was used to assess the area of lesions in vulvar LP. Results. The erosive form dominated in the structure of vulvar LP morbidity, which was diagnosed in 73,9% of cases. The process in erosive and hypertrophic form of LP was more common than in the typical form of LP. Distinctive features of the erosive form of the disease were the involvement of the inner surfaces of the labia minora and the vestibule (73,5% и 70,6%, p 0,001). The erosive LP is also characterized by a damage of normal vulvar architectonics (58,8%, p = 0,007). Lesions in typical LP affected labia majora (66,7%) and labia minora (33,4%), and to a lesser extent the commissure posterior (16,7%). The involvement of labia majora was found in all patients with hypertrophic form LP. The involvement of inguinal folds distinguished the hypertrophic form from other forms of LP and was observed in 33,4% of patients. Vulva lesions without the involvement of the skin and mucous membranes of other localizations were more typical for patients with erosive and hypertrophic LP (35,4% и 33,3%). Almost half of the patients (47,0%) with erosive LP had the involvement of mucous membranes, 29,0% of them were diagnosed with vulvovaginal-gingival syndrome. In 14.7% of cases, vulvovaginal-gingival syndrome combined with lesions in the scalp (vulvovaginal-gingival-pillar syndrome). Conclusions. We have identified clinical features of different forms of vulvar LP, which can be used for differential diagnosis.